Fintech and Financial Inclusion: A Study on the Role of P2P Lending Platforms for Unbanked MSMEs (UMKM) in Indonesia - I Putu Astawa; Kabelo Dube; Charles Ndikumana (Yayasan Adra Karima Hubbi, 2025)
Background. In Indonesia, micro, small, and medium enterprises (MSMEs), which represent a significant portion of the economy, often face challenges in accessing traditional financial services due to limited access to banking and credit facilities. Peer-to-peer (P2P) lending platforms have emerged as a viable alternative to address the financing gap for unbanked MSMEs. Purpose. This study investigates the role of P2P lending platforms in promoting financial inclusion among unbanked MSMEs in Indonesia, focusing on their potential to provide easier access to capital and foster economic growth. Method. The research adopts a mixed-methods approach, combining quantitative surveys and qualitative interviews with MSME owners and financial experts. A total of 200 MSMEs across various sectors were surveyed, and 15 in-depth interviews were conducted to explore the experiences of MSME owners using P2P lending services. Data analysis includes descriptive statistics and thematic analysis to understand the impact of P2P lending on business performance, financial inclusion, and economic empowerment. Results. The findings reveal that P2P lending platforms have significantly improved access to capital for unbanked MSMEs, enabling them to expand their operations and enhance their financial stability. However, challenges such as high-interest rates, limited awareness, and lack of financial literacy remain. Conclusion. The study concludes that P2P lending platforms play a crucial role in enhancing financial inclusion for MSMEs in Indonesia. To maximize their impact, there is a need for more targeted financial literacy programs and policy support to improve the accessibility and sustainability of these platforms for unbanked MSMEs.